Finlande-Québec au temps d’une décennie PISA : regards croisés de deux systèmes éducatifs - Guy Pelletier (Recherches en Éducation)
In education, during the 2000s, the Programme for International Student Assessment (PISA) had a tremendous impact on the analysis, assessment and evaluation of national educational systems of the Organisation for Economic Co-operation and Development (OECD) countries even though it was not conceived to that end and even though the PISA scores had not had the same effect in the past. However, it did so while other concerns emerged in a changing background: globalization, successive economical crises, loss of institutional and cultural landmarks, etc. This paper describes and makes a cross-analysis of the situation in Finland and Quebec. The paper uses a number of examples to illustrate the myth or problematic of looking at only the results of PISA scores as a means to value or valorise a system of education.